Role of Arbuscular Mycorrhiza Strains on Biomass Production and P, Cu, Zn Uptake in Prosopis cineraria - Verma, Neelam; Tarafdar, J. C.; Srivastava, K. K. (Indian Forester, 2010)
Prosopis cineraria was grown in a green house in a low phosphorus (4 mg kg-1 Olsen’s P) soil (Typic Camborthid) under arid environment inoculated with alone or mixed AM fungi either indigenous or from outside sources. Uptake of relatively immobile soil nutrients (P, Zn, Cu) as affected by different AM fungi was also studied. In general, significant and positive response of plant height, root and shoot biomass, root colonization and AM fungal population was observed in inoculated plants as compared to control. Inoculated plants had significantly higher P, Zn and Cu concentration as well as upto three times more total uptake. Mycorrhizal dependency to P. cineraria varied between 13.76 and 56.28%, which was more to Glomus aggregatum. In general, G. aggregatum was found to be the most efficient AM species for growth and nutrition of P. cineraria plant.